Rheological and thermal analysis of the filling stage of injection moulding - A. Szucs; K. Belina (eXPRESS Polymer Letters)
Flow conditions are different in the cavity of the injection mould from the capillary flow of a laboratory rheological instrument. An injection moulding slit die rheometer (Rheo-mould) was designed with a series of slit and orifice dies. Four pressure sensors were built in the stationary side of the mould, therefore the pressure could be measured at four different places. A changeable slit die insert was designed in the moving side. The shear stress and the shear rate can be calculated from the pressure gradient and from the flow rate of the melt, respectively. Flow curves of low density polyethylene were determined using Bagley, Rabinowitsch and Mooney corrections. The results were compared to the flow curves determined by Göttfert and Haake capillary equipments. It was found that the agreement between the methods is excellent.